ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN DALAM MENDUKUNG PENGENDALIAN INTERNAL DI PT. SINERGI KETAHANAN PANGAN - Ai Novi Pebrianti (2022)
This qualitative research aims to determine the sales accounting information system and internal control of the sales accounting information system at PT Sinergi Pangan Ketahanan Pangan. This study uses an interpretive paradigm with an ethnomethodological approach. Data collection techniques in this study used observation by participating in direct sales activities, conducting interviews with key informants and supporting informants, and doing documentation. The results of this study indicate that the implementation of the sales accounting information system at PT Sinergi Ketahanan Pangan has been running quite well and by existing theory. In addition, the company's internal control is mainly influenced by the Committee of Sponsoring Organizations (COSO) elements. However, in practice, it has not been fully implemented properly. It is still found that there is no credit function and general journal recording. In internal control, it is still found that there are double tasks due to minimal human resources, low quality of employees, lack of supervision, and the absence of separate assessments.